2014
DOI: 10.1016/j.ceb.2013.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Role of G protein-coupled receptor kinases in cell migration

Abstract: Esta es la versión de autor del artículo publicado en: This is an author produced version of a paper published in:Current Opinion In Cell Biology 27.1 (2014)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 58 publications
1
47
0
Order By: Relevance
“…G-protein-coupled receptor kinases represent critical nodes in cell migration processes. One of its isoforms, GRK2, has been established to play an effector role in chemotaxis, in the organization of actin and microtubule networks and in adhesion dynamics within an integrated system encompassing a variety of substrates and partners (18). It has been shown that GRK2 and GRK6, along with β-arrestin, bind CXCR4 causing its modulation.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…G-protein-coupled receptor kinases represent critical nodes in cell migration processes. One of its isoforms, GRK2, has been established to play an effector role in chemotaxis, in the organization of actin and microtubule networks and in adhesion dynamics within an integrated system encompassing a variety of substrates and partners (18). It has been shown that GRK2 and GRK6, along with β-arrestin, bind CXCR4 causing its modulation.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…The astrocytosis observed differed from conventional astrocytosis, which is associated with neuronal loss and neuroinflammation, suggesting that it occurred in a cell-autonomous manner. GIT1 plays a critical role in cell migration and polarization (Penela et al, 2014); therefore, an increase in the number of astrocytes in specific brain regions may be the result of abnormal cell migration. Moreover, the small GTPase, Rac1, is required for cell polarization, directed migration (Fukata et al, 2003), and regulation of astrocytic migration (Etienne-Manneville and Hall, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that GRK2 is highly expressed in different types of immune cells, and it can attenuate the chemokine-induced migration of T cells and monocytes as a relevant modulator of inflammation [77]. GRK2 phosphorylates chemotactic GPCRs, such as CCR5, CCR2b, CXCR4, and CXCR2, and chemotactic receptors for substance P, S1P or formyl-peptide, and can also modify PDGF or EGF plasma membrane tyrosine kinase receptors, cytoskeleton proteins (ezrin and tubulin), p38MAPK, and metabotropic glutamate receptors, which contribute to leukocyte trafficking to inflammatory foci, T cell egression from lymphoid organs, and leukocyte activation or proliferation [78].…”
Section: Resultsmentioning
confidence: 99%